Morocco / Rachida Alaoui, Jean Brignon, Nathalie Campodonico,... - Alaoui, Rachida Author
"The flavors of Morocco, region by region; cutaways and floor plans of all the major sights; tailor-made itineraries to help you make the most of your stay; huge selection of hotels and restaurants; sights, beaches, markets, and festivals listed town by town; walks, scenic routes, and thematic tours"